Do Self-Objectified Women Believe Themselves to Be Free? Sexual Objectification and Belief in Personal Free Will - Baldissarri, Cristina; Andrighetto, Luca; Gabbiadini, Alessandro; Valtorta, Roberta Rosa; Sacino, Alessandra; Volpato, Chiara (Frontiers in Psychology, 2019)
The present study aims to investigate the indirect link between sexual objectification and belief in personal free will. We hypothesized that being subjected to objectifying commentary would lead women to self-objectify and, in turn, to perceive themselves as having less personal free will. In this study, 105 women were asked to sign up a website created for this study by providing a personal description and a photo. After signing up, they received feedback from a fictitious male user. Depending on the condition, the comment was neutral (baseline), focused on their description (non-objectifying) or focused on their physical appearance (objectifying). The results showed that participants in the objectifying condition (vs. non-objectifying vs. baseline) self-objectified (i.e., perceived themselves as lacking human mental states and more as an instrument vs. a human) and, in turn, believed that they had less personal free will. The theoretical and practical implications of these findings for educators and therapists are discussed.